Religious Affiliation and Work–Family Conflict Among Women and Men. (May 2018) - May, Matthew; Reynolds, Jeremy
Religion is an important part of life for many women and men. Research on religion and work–family issues, however, remains limited. To better understand how religion influences work–family experiences, we use data from the General Social Survey to examine subjective experiences of work–family conflict across three religious groups and the nonreligious. Specifically, we examine how conservative Protestants, Catholics/Orthodox Christians, mainline Protestants, and the nonreligious differ in their perceptions of work-to-family and family-to-work conflict. We find that conservative Protestant women, but not men, report less work-to-family conflict and less family-to-work conflict than their peers in other religious groups even after controlling for religious service attendance, specific job features, and sociodemographic characteristics. Catholic/Orthodox men report less family-to-work conflict than conservative Protestant men. We suggest that researchers examine religion more closely to determine if the experiences of conservative Protestant women and Catholic/Orthodox men hold useful lessons for others.